Applying Machine Learning Techniques in Older People Activity Recognition usingWearable and Mobile Devices - Santana, Flavio Vinicius Vieira; Rasteiro, Bruno Henrique; Zimmermann, Larissa Cardoso; De Nardin, Luciana; Pimentel, Maria da Graça Campos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
We investigate the potential of the combined use of smartwatch accelerometer data and smartphone apps for online older adultsactivity recognition.We selected machine learning algorithms which resulted in a posteriori recognition accuracy of 98.92%. Our smartphone app, with the selected machine learning algorithms, carried out online recognition from data captured on the smartwatch. These results allow us, as future work, assess the accuracy of online recognition when the system is used by older adults.